Effects of AV3V lesion on pilocarpine-induced pressor response and salivary gland vasodilation - Takakura, ACT; Moreira, T. S.; De Luca, L. A.; Renzi, Antonio [UNESP]; Menani, José Vanderlei [UNESP]; Colombari, Eduardo [UNESP] (Elsevier B.V., 2005)
The cholinergic agonist pilocarpine injected intraperitoneally (ip) increases mean arterial pressure (MAP) and superior mesenteric (SM) vascular resistance and reduces submandibular/sublingual gland (SSG) vascular resistance. In the present study, we investigated the effects of electrolytic lesions of the anteroventral third ventricle (AV3V) region on the changes in MAP, SM, and SSG vascular resistances induced by ip pilocarpine. Male Holtzman rats anesthetized with urethane (1.0 g/kg) and chloralose (60 mg/kg) were submitted to sham or electrolytic AV3V lesions and bad pulsed Doppler flow probes implanted around the arteries. Contrary to sham rats, in 1-h and 2-day AV3V-lesioned rats, pilocarpine (4 mu mol/kg) ip decreased MAP (-41 +/- 4 and -26 4 mm Hg, respectively, vs. sham: 19 +/- 4 mm Hg) and SM (-48 +/- 11 and -45 +/- 10%, respectively, vs. sham: 41 +/- 10%) and hindlimb vascular resistances (-65 +/- 32 and -113 +/- 29%, respectively, vs. sham: 19 +/- 29%). In 7-day AV3V-lesioned rats, pilocarpine produced no changes on MAP and SM and hindlimb vascular resistances. Similar to sham rats, pilocarpine reduced SSG vascular resistance 1 h after AV3V lesions (-46 +/- 6%, vs. sham: -40 +/- 6%), but it produced no effect 2 days after AV3V lesions and increased SSG vascular resistance (37 6%) in 7-day AV3V-lesioned rats. The responses to ip pilocarpine were similar in 15-day sham and AV3V-lesioned rats. The cholinergic antagonist atropine methyl bromide (10 nmol) iv slightly increased the pressor response to ip pilocarpine in sham rats and abolished for 40 min the fall in MAP induced by ip pilocarpine in 1-h AV3V-lesioned rats. The results suggest that central mechanisms dependent on the AV3V region are involved in the pressor responses to ip pilocarpine. Although it was impaired 2 and 7 days after AV3V lesions, pilocarpine-induced salivary gland vasodilation was not altered 1 h after AV3V lesions which suggests that this vasodilation is not directly dependent on the AV3V region. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: cholinergic muscarinic receptor; salivation; arterial pressure; hypertension; 3rd ventricle